2001
DOI: 10.1097/00005537-200108000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of Chronic Frontal Sinusitis

Abstract: This study suggests that organisms involved in chronic inflammatory disease of the frontal sinus may change after previous sinus surgery. The study failed to support a significant role for anaerobes. The role for coagulase-negative Staphylococcus as a potential pathogen or a contaminating agent remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 12 publications
(18 reference statements)
0
18
1
1
Order By: Relevance
“…Accordingly, our literature review revealed that the different studies used a diversity of sampling methods (swabs, aspiration, molecular techniques) and sampling sites (middle meatus, maxillary sinus, other ethmoidal bulla, and frontal sinus), but none identified a distinct pattern of bacterial growth or a specific culprit species. The results of the most recent publications are summarized in table 1 [11,12,13,14,15,27,28,29]. …”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, our literature review revealed that the different studies used a diversity of sampling methods (swabs, aspiration, molecular techniques) and sampling sites (middle meatus, maxillary sinus, other ethmoidal bulla, and frontal sinus), but none identified a distinct pattern of bacterial growth or a specific culprit species. The results of the most recent publications are summarized in table 1 [11,12,13,14,15,27,28,29]. …”
Section: Discussionmentioning
confidence: 99%
“…42 The interactions between the bacteria related to chronic frontal sinusitis 43 and BAG have not been studied but, in principle, the experimentally shown antibacterial properties of BAG 35,36 can promote the clinical outcome of obliterated sinuses after chronic infection. Probably the antibacterial properties of BAG can provide extraordinarily favorable conditions for an uneventful healing process in a chronically infected environment.…”
Section: Discussionmentioning
confidence: 99%
“…13 On this basis, initial antibiotic therapy for chronic frontal sinusitis does not significantly differ from that for acute bacterial frontal sinusitis, with amoxicillin with clavulanate providing adequate coverage on an empiric basis, albeit for longer initial durations. Although the microbiology of acute bacterial frontal sinusitis lends itself to narrow-spectrum antimicrobial therapy, antibiotic therapy for either initial medical management or acute exacerbations of chronic frontal sinusitis may require broader-spectrum therapy and also may be more likely to result in treatment failures.…”
Section: Antibiotic Therapymentioning
confidence: 99%